The Relationship between Fulfilling Privacy Needs and Service Satisfaction in Adolescents with Chronic Illness Conditions in the Inpatient Room - Ihsar, Aini Hayati; Mediani, Henny Suzana; Fitri, Siti Yuyun Rahayu (Universitas Pendidikan Indonesia, 2021)
ABSTRACTIntroduction : Privacy needs for adolescents with chronic disease conditions are important, including secure information, psychological information, and social privacy. Violations against privacy will bring discomfort, stress, and dissatisfaction. Patients' satisfaction is one of the most important indicators that show the quality of ward services that include the dimensions of tangibility, reliability, responsiveness, assurance, and empathy. Objectives : This study was conducted to analyze the relationship between the fulfilment of privacy needs and service satisfaction in adolescents with hospitalized chronic conditions. Methods : This correlational study was conducted using a cross-sectional approach. Samples were 72 adolescents aged 12-21 years with chronic disease conditions were selected using the consecutive sampling method. Data of this study were collected using questionnaires. Bivariate data analysis was performed using chi-square analysis. Result : The results showed that the most unfulfilled need for privacy security was information privacy (70.8%), followed by psychological privacy (63.9%), physical privacy (58.3%), and the least unfulfilled one was social privacy (51.4%). Respondents were most dissatisfied with the dimension of empathy (87.5%), followed by assurance (84.7%), reliability (83.3%), tangibility (80.6%), and responsiveness (76.4%). This study also confirmed a meaningful relationship between service satisfaction with information privacy (p-value 0.001) and physical privacy (p-value 0.021 0.05). Discussion : Whereas service satisfaction is associated with neither psychological privacy nor social privacy. The role of nurses is very important in carrying out patient-centered care, especially in meeting the privacy needs to achieve service satisfaction for adolescents with chronic disease conditions.ABSTRAKPendahuluan : Kebutuhan privasi pada remaja dengan kondisi penyakit kronis merupakan suatu hal yang penting meliputi privasi informasi, fisik, psikologis dan sosial karena jika tidak terpenuhi akan menimbulkan ketidaknyamanan, stress dan ketidakpuasan. Kepuasan merupakan salah satu indikator paling penting untuk menunjukan kualitas pelayanan di ruang rawat inap mencakup dimensi tangibles, reliability, responsiveness, assurance, dan empathy. Tujuan : Tujuan penelitian ini menganalisis hubungan pemenuhan kebutuhan privasi dengan kepuasan layanan pada remaja kondisi penyakit kronis di ruang rawat inap. Metode : Desain penelitian studi korelasional dengan pendekatan cross sectional. Jumlah sampel pada penelitian ini adalah remaja usia 12-21 tahun dengan kondisi penyakit kronis berjumlah 72 orang dengan metode consecutive sampling. Pengumpulan data menggunakan kuesioner. Analisis data bivariat menggunakan chi square. Hasil : Hasil penelitian menunjukan bahwa paling banyak kebutuhan privasi yang tidak terpenuhi adalah privasi informasi sebanyak 70,8%, diikuti privasi psikologis sebanyak 63,9%, privasi fisik 58,3%, dan paling sedikit tidak terpenuhi adalah privasi sosial sebanyak 51,4%. Responden paling banyak tidak puas dalam dimensi emphaty sebanyak 87,5%, urutan kedua dimensi assurance sebanyak 84,7%, urutan ketiga dimensi reliability sebanyak 83,3%, urutan keempat dimensi tangibles sebanyak 80,6%, dan yang kelima dimensi responsiveness sebanyak 76,4%. Terdapat hubungan antara kepuasan layanan dengan privasi informasi (p-value 0,001) dan privasi fisik (p-value 0,021 0,05), sedangkan dengan privasi psikologis dan sosial tidak memiliki hubungan. Diskusi. Peran perawat sangat penting dalam melakukan asuhan dengan berpusat pada pasien terutama dalam memenuhi kebutuhan privasi agar tercapainya kepuasan layanan terhadap remaja dengan kondisi penyakit kronis.